Impact of impurities on zonal flow driven by trapped electron mode turbulence. (13th October 2017) - Guo, Weixin; Wang, Lu; Zhuang, Ge
Abstract: The impact of impurities on the generation of zonal flow (ZF) driven by collisonless trapped electron mode turbulence in deuterium (D)–tritium (T) plasmas is investigated. An expression for ZF growth rate with impurities is derived by balancing the ZF potential shielded by polarization effects and the ZF modulated radial turbulent current. Then, it is shown that the maximum normalized ZF growth rate is reduced by the presence of fully ionized non-trace light impurities with relatively flat density profile, and slightly reduced by highly ionized trace tungsten, while the maximum normalized ZF growth rate can be enhanced by fully ionized non-trace light impurities with relatively steep density profile. In particular, the effects of high temperature helium from D–T reaction on ZF depend on the temperature ratio between electrons and high temperature helium. The possible relevance of our findings to recent experimental results and future burning plasmas is also discussed.